Effect of construction stages on the settlement of dikes - Mak, Kelvin Kin Weng (2014)
This project explores what are the effects of staged construction and lowering of mean sea-level has on the settlement and dissipation of excess pore pressure of the seabed within a polder system. The methodology presented is based on parametric information gained from previous studies and extensive use of Finite Element Model (FEM) simulation software, PLAXIS 2D, to model the dike construction and simulate results of settlement and dissipation of excess pore pressure